Statistical Assessment of the Effect, Efficiency and Intensity of the Hotel & Tourism Industry in Ukraine - Zakhozhai, V. B.; Savytskyi А. V. (Statistics of Ukraine, 2025)
The article is devoted to methodological and practical dimensions of statistical assessment of the effect, efficiency, and intensity of the hotel & tourism industry in Ukraine. The aggravated social and economic crisis, COVID-19 pandemic and warfare changed tourist flows, priorities of demand, and regional preferences, thus necessitating a revision of the principles underlying intra-industry reforms. The need for creating standardized approaches to collecting, processing, analysis and economic interpretation of industry-specific statistical data was substantiated. The article’s objective is to elaborate a set of indicators, methods and rules enabling to determine the performance of the hotel & tourism industry and its segments given the efficient utilization of the resource capacity. The methodological framework consists of dialectical and structural-logical approaches, methods of system analysis, statistical modelling and forecasting. The results of research cover determined principles of the industry’s efficiency, identified principal factors, and recommended comprehensive statistical monitoring using advanced tools of policy, observation and forecasting. A method for factor analysis of the effect, efficiency, and intensity of the hotel & tourism industry and its structural segments was proposed. The research novelty is in systematizing the indicators for assessment of the hotel & tourism complex from the sustainability perspective, and in adapting international standards UN Tourism and Eurostat standards to the national observation practice. Attention was drawn to harmonizing the national statistical framework with European classifications of economic activities, introducing digital technologies for recording and computerization of data collection in the hotel & tourism industry. Emphasis was made on the importance of incorporating the results of statistical analysis into strategic documents of regional development, to enhance the analytical capacity of management decisions and build an efficient model for recovering of the hotel & tourism industry. The practical value of this work is in the applicability of the proposed approaches in taking optimal management decisions, elaborating algorithms and actions designed to enhance the efficiency of the hotel & tourism industry in Ukraine in view of the current challenges and postwar recovery.